2023
DOI: 10.1001/jamanetworkopen.2023.44517
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Disparity in Preoperative Chemosensitivity and Survival in Patients With Early-Stage Breast Cancer

Arya Mariam Roy,
Archit Patel,
Kayla Catalfamo
et al.

Abstract: ImportanceIt remains unclear what survival benefit is associated with preoperative chemosensitivity after receiving neoadjuvant chemotherapy (NACT) among patients with resectable breast cancer from diverse racial and ethnic backgrounds.ObjectiveTo investigate racial and ethnic disparities in chemosensitivity and association with survival in patients with early-stage breast cancer.Design, Setting, and ParticipantsThis retrospective cohort study queried data from the National Cancer Database (NCDB) between calen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
(51 reference statements)
1
0
0
Order By: Relevance
“…Similar findings were recently reported by Roy et al 29 who assessed racial differences in chemosensitivity (very sensitive = pCR, sensitive = partial response, refractory = no response) among all breast cancer subtypes; they demonstrated that among patients with TNBC, Black women had the lowest rates of very sensitive (25.7%) and the highest rates of refractory disease (38% v 30%-35%; P < .001). However, when Black women achieved pCR, OS did not differ from White (hazard ratio, 0.99 [95% CI, 0.82 to 1.18], P = .23).…”
Section: Discussionsupporting
confidence: 88%
“…Similar findings were recently reported by Roy et al 29 who assessed racial differences in chemosensitivity (very sensitive = pCR, sensitive = partial response, refractory = no response) among all breast cancer subtypes; they demonstrated that among patients with TNBC, Black women had the lowest rates of very sensitive (25.7%) and the highest rates of refractory disease (38% v 30%-35%; P < .001). However, when Black women achieved pCR, OS did not differ from White (hazard ratio, 0.99 [95% CI, 0.82 to 1.18], P = .23).…”
Section: Discussionsupporting
confidence: 88%
“…Another study showed a higher number of TILs in Asians and Native Hawaiian/Pacific Islanders [36]. This difference in the immune microenvironment can play a role in the responses of different races to immunotherapy [23]. However, most of the trials in our meta-analysis did not have subset analysis based on race, so we could not assess the association of race and pCR/survival in our meta-analysis [34].…”
Section: Discussionmentioning
confidence: 93%
“…The presence of residual disease after neoadjuvant treatment is associated with higher relapse rates in TNBC patients [21]. Although we utilize pCR as an endpoint in clinical trials utilizing neoadjuvant systemic treatments, a longer follow-up time through which to assess EFS and OS is necessary, as pCR might not necessarily translate to better clinical response in some patients, especially in certain racial groups and in certain breast cancer subtypes [22,23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation